Adding fat to sow lactation diets: effect on sow and litter performance - D Keesecker; B Wolf; Michael D Tokach; Jim L Nelssen (Kansas Agricultural Experiment Station Research Reports, 1986)
An on-farm experiment was conducted utilizing 189 sows to evaluate the effect of adding 396 soybean oil to the lactational diet on subsequent pig performance and sow weight loss. Feeding sows a diet containing 3% soybean oil during lactation did not significantly decrease sow weight loss or improve litter performance. However, the oil addition tended to increase individual pig weaning weight (.5 Ib), litter weaning weight (3 lb), and sow feed intake (.5 lb/day) compared to feeding a 14% crude protein milo-soybean meal diet. Also, sow lactational weight loss was slightly reduced wit h the diet containing oil. Calculated metabolizable energy intake was increased (P<.01) for sows fed the diet with soybean oil compared to sows fed the control diet. We postulate that the increased calorie intake from adding soybean oil to sow lactation diets during the summer months may increase litter weaning weight.; Swine Day, Manhattan, KS, November 20, 1986
Keywords: Swine day; 1986; Kansas Agricultural Experiment Station contribution; no. 87-133-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 507; Swine; Sow; Lactation; Performance